Flyboys [videorecording (DVD)] - Evans, Blake T.; Sears, Phil; Ward, David S., 1945-; Franco, James, 1978-; Henderson, Martin, 1974-; Hazell, Scott, 1987-; McDonald, Mac, 1949-; Winchester, Philip, 1981-; Boyce, Todd, 1961-; Jibson, Michael; Ford, Karen, 1946-; Ellison, David, 1983-; et al. (Metro-Goldwyn-Mayer Studios, 2006)
A story of the young Americans who volunteered to be part of the French military prior to the United States involvement in WWI, also known as Lafayette Escadrille, and how they became the country's first fighter pilots.